Views from the Top and Bottom: Lawmakers and Practitioners Discuss Sex Offender Laws - Meloy, Michelle (American journal of criminal justice, 2013)
The perceptions and attitudes that policymakers and criminal justice practitioners have about sexual offending and sexual victimization affects how state lawmakers respond to sex crimes, and how practitioners implement sex offender legislation. Policymakers continue to create new sex offender laws and, as such, the number of convicted sex offenders continues to rise. Thus, policymakers and criminal justice practitioners are increasingly important players in the public policy response to sexual criminals. To better understand the motivation, rationale, content, and purpose of statewide sex offender laws, and their role in the day-to-day management of convicted sex offenders, a non-probability sample of policymakers ( n = 61) and criminal justice practitioners ( n = 25) from across the country were interviewed. Results indicated that nearly all respondents from both groups were familiar/very familiar with their state-level sex offender laws. Policymakers and practitioners also mentioned the influential role that specific victimizations play in creating a perceived need for more sex offender legislation. The politicians and the practitioners view the laws as effective public safety mechanisms. Still, both groups noted serious problems with the laws. Furthermore, policymakers had a more negative attitude about the efficacy of sex offender therapy than criminal justice respondents. Suggestions for future research and policy implications are offered.